Narrative identities and the plebiscite in Pará: an analysis of the front pages for O Liberal and Diário do Pará - COSTA, Alda Cristina Silva da (Associação Brasileira de Pesquisadores em Jornalismo, 2022)
On December 11, 2011, a plebiscite was held in Pará proposing to create two separatist states, Carajás and Tapajós, out of the state of Pará. The public voted against both projects. This article analyzes the narrative identities found on the front pages of O Liberal and Diário do Pará newspapers about the plebiscite in Pará. Depth Hermeneutics (DH), as proposed by Thompson (2011), was used as the methodological reference. DH emphasizes the object of analysis as a meaningful symbolic construction requiring interpretation. Narrative analysis, as proposed by Motta (2007), was the main research technique used to highlight the movement of construction of journalistic (discursive) characters. The narrative identities built by the two newspapers showed that both were against the creation of the new states, but for very different reasons. The flag of Pará was the main object used to induce the idea of unity.